An Overview of the Temporal Shedding of SARS-CoV-2 RNA in Clinical Specimens - Zhurakivska, Khrystyna; Troiano, Giuseppe; Pannone, Giuseppe; Caponio, Vito Carlo Alberto; Lo Muzio, Lorenzo (Frontiers in Public Health, 2020)
Coronavirus disease 2019 quickly spread in China and became pandemic from March 2020, causing hundreds of thousands of deaths worldwide. The causative agent was promptly isolated and named SARS-CoV-2. Scientific efforts are related to identify the best clinical management of these patients, but also in unserstanding their infectivity in order to limit the spread of the virus. Aimed in identifying viral RNA in the various compartments of the organism of the sick subjects diagnostic tests are carried out. However, the accuracy of such tests varies depending on the type of specimen and the time of illness in which they are performed. This review of the literature aim to summarize the preliminary findings reported in the papers on the Covid-19 them. The results highlight how the pharyngeal swab is highly sensitive in the first phase of the disease, while in the advanced stages, other specimens should be considered, such as sputum, or even stool to detect SARS-CoV-2 positivity. It highlights, even as most of the patients in the first days of symptoms, already reach the peak of the viral load in the upper airways, which then tends to decrease. This suggests that many patients may already be infectious before symptoms appear.